A smart system for twitter corpus collection, management and visualization - Brogueira, G. (2017)
Social networks have become popular and are now becoming an alternate mean of communication, used to share information on various topics, ranging from politics or sports to simple aspects of everyday life. Twitter messages (tweets) are shared in real time and are essentially public, making them a useful source of information for areas such as tourism, marketing, health, and safety. This paper describes an information system that involves the creation and storage of a corpus of tweets, written in European Portuguese and published within the Portuguese territory. The system also involves a REST API that allows access to the stored information, and a web-based dashboard that makes it possible to analyze and visualize indicators concerning the stored data.